PENGARUH IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING TERHADAP HASIL BELAJAR SISWA KELAS III SD IT BANI SHIDDIQ - Jejen Jenal Aripin; Nana Sutarna (STKIP Subang, 2024)
The purpose of this study was to determine the effect of the application of the Project Based Learning model on student learning outcomes. The method used in this research is pre-experiment method with One Group Pretest-Posttest design. The research was conducted at Bani Shiddiq Integrated Islamic Elementary School, involving 20 third grade students of the Integrated Islamic Elementary School as research subjects. The instruments used to measure student learning outcomes were pretest and posttest tests. The pretest was conducted before the learning process to measure students‘ initial knowledge, while the posttest was conducted after the learning process to assess the improvement of students’ understanding and skills. The hypothesis test results showed a significance value of 0.000. Since the significance value of 0.000 <0.05, the null hypothesis (H0) is rejected and the alternative hypothesis (H1) is accepted. So it can be concluded that there is a significant difference in the cognitive learning outcomes of grade III SDIT Bani Shiddiq students, towards improving student learning outcomes by using the Project Based Learning model. In addition, the N-Gain test results show a value of 0.5649 which is included in the medium criteria which indicates an increase in student learning outcomes. Thus it can be concluded that there is an effect of the Project Based Learning model.